Phase transformation and microstructural development of zirconia/stainless steel bonded with a Ti/Ni/Ti interlayer for the potential application in solid oxide fuel cells. Issue 8 (9th April 2014) - Wei, Shen-Hung; Lin, Chien-Cheng
Abstract